NPK FERTILIZER SLOW RELEASE WITH ZEOLITE AS ONE FILLER AT TEA GARDEN - Pudjo Rahardjo (Jurnal Zeolit Indonesia, 2008)
The fertilizer is one of factors production besides land, water, seed, and cultivation technology. Without giving fertilizer which suitable with recommendation the needs of the plants to fulfill nutrient balance, potential product or potential of plant genetics will not be achieved. Proper fertilizer is giving fertilizer with exactly type, right dosage, correct method and time, and effectively to increase productivity, and economics efficiency. This is contained in slow release fertilizer which wearing zeolite filler. NPK fertilizer slow release using zeolite as one of filler with ratio of N:P:K:Mg = 25:5:10:2 and 23:7:10:2 with doses of 400, 600, and 800 kg/ha/year applied on two times a year. Whereas, recommended doses is using a singular fertilizer of N= 300, P2O5 = 94, K2O = 180, MgO = 54 kg/ha/year, 4 applications/year. Dosage of 800 kg/ha/year of formula I and formula II was increasing treetops. Dosage of 400 kg/ha/year and 600 kg/ha/year giving lower treetops. It is compared with the control without fertilizer treatment was showed a significant increase (115 to 129%) in clones of tea 2025 in Tea Garden Canaan.